Peoples and Borders: Seventy Years of Migration in Europe, from Europe, to Europe [1945-2015] - Calandri, Elena; Paoli, Simone; Varsori, Antonio (Nomos Verlagsgesellschaft mbH & Co. KG, 2017)
Movement of people has been a key feature in the whole history of European integration. While existing literature has mostly adopted national viewpoints and a socioeconomic perspective, this book integrates these existing fragmented analyses, views them from a broader perspective and places them in the wider context of the social and demographic transformation of Europe and the political and economic narrative of continental integration. It highlights the impact made by EC/EU immigration policies on the external political and economic relations of Europe and acknowledges that pre-1989 migration from East European countries is part of European integration. By showing that migration policies and their impact on European national societies and economies cannot be fully understood without taking into account the EC framework, this book, therefore, contributes to migration studies as a whole.